Locomotor Training Increases Synaptic Structure With High NGL-2 Expression After Spinal Cord Hemisection. (March 2019) - Kobayakawa, Kazu; DePetro, Kyleigh Alexis; Zhong, Hui; Pham, Bau; Hara, Masamitsu; Harada, Akihito; Nogami, Jumpei; Ohkawa, Yasuyuki; Edgerton, V. Reggie
Background . We previously demonstrated that step training leads to reorganization of neuronal networks in the lumbar spinal cord of rodents after a hemisection (HX) injury and step training, including increases excitability of spinally evoked potentials in hindlimb motor neurons. Methods . In this study, we investigated changes in RNA expression and synapse number using RNA-Seq and immunohistochemistry of the lumbar spinal cord 23 days after a mid-thoracic HX in rats with and without post-HX step training. Results . Gene Ontology (GO) term clustering demonstrated that expression levels of 36 synapse-related genes were increased in trained compared with nontrained rats. Many synaptic genes were upregulated in trained rats, but Lrrc4 (coding NGL-2) was the most highly expressed in the lumbar spinal cord caudal to the HX lesion. Trained rats also had a higher number of NGL-2/synaptophysin synaptic puncta in the lumbar ventral horn. Conclusions . Our findings demonstrate clear activity-dependent regulation of synapse-related gene expression post-HX. This effect is consistent with the concept that activity-dependent phenomena can provide a mechanistic drive for epigenetic neuronal group selection in the shaping of the reorganization of synaptic networks to learn the locomotion task being trained after spinal cord injury.